Sport as an educational practice - Francesca Caso; Francesco Tafuri (Pensa MultiMedia, 2022)
By promoting positive values though physical activity, sport acts as a fundamental educational tool. The analysis of pedagogical theories and educational experimentations show the way sport can promote effective and constructive qualities, thanks to conscious student-centered projects and a careful use of active learning strategies for the promotion of life skills. The purpose of this paper is to highlight the practices and strategies that can determine the art of "sport" in an educational perspective. Nowadays, sport can overcome cultural and social barriers thanks to more performing methodologies that are close to the new generations. The innovative and educational development of sports activities is effective, and can facilitate and support the educational growth of the community, especially that of the youth.